Individual Differences and Susceptibility to Burnout Syndrome: Sensory Processing Sensitivity and Its Relation to Exhaustion and Disengagement - Golonka, Krystyna; Gulla, Bożena (Frontiers in Psychology, 2021)
The aim of the study is to analyze the relationship between sensory processing sensitivity and occupational burnout. This analysis makes it possible to explore the problem of sensitivity as a predictor of burnout syndrome and to discuss adequate coping strategies in the work environment to improve employee well-being. The sample consists of 516 employees (236 women; Mage = 28.97, SD = 6.62 years). The Highly Sensitive Person Scale (HSPS) and the Oldenburg Burnout Inventory (OLBI) were used in the study. The analysis of sensitivity is based on the ‘DOES’ model of a highly sensitive person, which includes depth of processing (D), overstimulation (O), emotional reactivity and empathy (E), and sensing the subtle (S). Burnout due to exhaustion and disengagement is analyzed. The factor analysis of the HSPS confirms its three-factor structure. The results indicate significant relationships between sensory processing sensitivity and burnout symptoms. However, the influence of specific aspects of sensitivity on the burnout problem varies: the results indicate that higher emotional reactivity is linked to worse burnout symptoms, but sensing the subtle shows the opposite effect and may be a protective factor against exhaustion. Significant gender differences were observed (F(511,1) = 136.63, p < 0.001; eta2partial = 0.21); women revealed a significantly higher level of general sensitivity (Mwomen = 4.66, SD = 0.62) as compared to men (Mmen = 4.01; SD = 0.64). Awareness of one’s high sensory-processing sensitivity and its potential outcomes in the work environment may be essential in order to implement appropriate regulatory strategies. Proactive strategies aimed at reducing prolonged emotional overload may be critical for highly sensitive employees. Recognizing high sensitivity may reduce burnout symptoms and improve well-being at work.